Rapid rise in COVID-19 among young people in England – learning for the future. (May 2023) - Twohig, K.A.; Zaidi, A.; Campos-Matos, I.; Hope, R.; Hall, J.; Chudasama, D.; Sinnathamby, M.; Fitzpatrick, J.; Dabrera, G.; Mohammed, H.
Abstract: Objectives: We determined the age and sociodemographic distribution of COVID-19 cases between January and September 2020 to identify the group with the highest incidence rates at the beginning of the second wave in England. Study design: We undertook a retrospective cohort study design. Methods: SARS-CoV-2 cases in England were linked with area-level socio-economic status indicators using quintiles of the Index of Multiple Deprivation (IMD). Age-specific incidence rates were stratified by IMD quintile to further assess rates by area-level socio-economic status. Results: Between July and September 2020, SARS-CoV-2 incidence rates were highest amongst those aged 18–21 years, reaching rates of 213.9 (18–19 years) and 143.2 (20–21 years) per 100, 000 population by week ending 21 September 2022. Stratification of incidence rates by IMD quintile evidenced that despite high rates observed in the most deprived areas of England amongst the very young and older age groups, the highest rates were observed in the most affluent areas of England amongst the 18- to 21-year-olds. Conclusions: The reversal of sociodemographic trend in COVID-19 cases in England for those aged 18–21 years at the end of the summer of 2020 and beginning of the second wave showed a novel pattern of COVID-19 risk. For other age groups, the rates remained highest for those from more deprived areas, which highlighted persisting inequalities. Combined, this demonstrates the need to reinforce awareness of COVID-19 risk for young people, particularly given the late inclusion of the 16–17 years age group for vaccination administration, as well as continued efforts to reduce the impact of COVID-19 on vulnerable populations.